2013
DOI: 10.1016/j.appet.2012.10.020
|View full text |Cite
|
Sign up to set email alerts
|

What’s (in) a real smoothie. A division of linguistic labour in consumers’ acceptance of name–product combinations?

Abstract: Is being, say, a macaroon or a smoothie a matter of what these products look and taste like and how they feel in the mouth? Or is it a matter of which ingredients have been used and how they have been processed? Will ordinary consumers always rely on their own judgment in such matters, or delegate the final judgment to experts of some sort? The present experimental study addressed these issues in combination by testing the limits for consumers' acceptance of three different name-product combinations when expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 32 publications
0
7
0
4
Order By: Relevance
“…if the design possessed assay sensitivity [18]. Three components of typical smoothies, water, energy and the bioactive compounds derived from berries, fruits and vegetables, could hypothetically play a role in improving children’s academic performance [1,4,11,12,21]. In our study, the results obtained from the d2 test of attention indicated an effect of water and energy supplementation, with both groups exhibiting an increase in performance – measured as speed (PTO) and concentration (CP) – following the consumption of both the active and control beverages.…”
Section: Discussionmentioning
confidence: 99%
“…if the design possessed assay sensitivity [18]. Three components of typical smoothies, water, energy and the bioactive compounds derived from berries, fruits and vegetables, could hypothetically play a role in improving children’s academic performance [1,4,11,12,21]. In our study, the results obtained from the d2 test of attention indicated an effect of water and energy supplementation, with both groups exhibiting an increase in performance – measured as speed (PTO) and concentration (CP) – following the consumption of both the active and control beverages.…”
Section: Discussionmentioning
confidence: 99%
“…In Fig. 2(B-D), the F1 axis explained 51.61%, 46.14% and 51.44% of the total data variance in the fig (samples 1-4), jujube (samples M Cano-Lamadrid et al [5][6][7][8] and quince (samples 9-12) smoothies, respectively; while the axis F2 explained 31.16%, 42.31% and 33.51% of the total variance, respectively.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 92%
“…A good option to benefit from the nutrients and bioactive compounds responsible for healthy effects of fruits and vegetables is the consumption of smoothies containing carrot, broccoli, tomato, sour cherry, apple and Prunus fruits . A 'smoothie', from the English word 'smooth' (tender, creamy) is a creamy drink (the texture is thick, similar to that of milkshakes) made from blended fruit (purée) together with fruit juice, and perhaps yoghurt or other dairy products and/or crushed ice cubes …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ciò è in linea con l'ipotesi di Putnam (1975) sulla divisione del lavoro linguistico. Tre aspetti della sua teoria appaiono qui rilevanti: il primo è che i membri della società collaborano per cercare di concordare il significato esatto delle parole che usano; il secondo è che la maggioranza degli utenti di una lingua collega per lo più le parole a 'stereotipi' vaghi e non proprio identici, che sono tuttavia sufficienti a garantire la mutua comprensione nella gran parte delle situazioni; il terzo, infine, è che ogni qual volta insorge un dubbio la comunità linguistica demanda il giudizio finale a quei membri della società che godono dello status di 'esperti' (Smith et al 2013). Ogni volta che ciò accade, si ha un esempio di terminologizzazione, cioè il fatto che a una parola comunemente nota può essere attribuito, all'interno di un campo professionale ristretto, un significato più specifico rispetto a quello che possiede nella lingua generica (Ahmad and Rogers 2007).…”
Section: Oggettività E Soggettività Dell ' Esperienzaunclassified